Micromass culture of human anulus cells: morphology and extracellular matrix production - Gruber, Helen E; Chow, Yin; Hoelscher, Gretchen L; Ingram, Jane A; Zinchenko, Natalia; Norton, H James; Sun, Yubo; Hanley, Jr, Edward N (Spine (Philadelphia, Pa. 1976), 2010)
Micromass culture was assessed as a cell culture microenvironment for anulus cells from the human intervertebral disc. To determine whether the micromass culture technique might be useful for the culture of human anulus cells. Culture of cells in micromass has been traditionally used as a method to culture chondrocytes in a three-dimensional (3D) microenvironment with specialized chondrocyte media which allows expression of the chondrocytic phenotype. Recently it has also been used for disc cell 3D culture. Following approval of our human subjects Institutional Review Board, cells isolated from human anulus intervertebral disc tissue was cultured in micromass culture under control conditions or with addition of 5 ng/mL transforming growth factor-beta (TGF-beta). Cultures were grown for 7 days, and then analyzed for morphology with light microscopy, for extracellular matrix (ECM) production with transmission electron microscopy and quantitative measurement of total sulfated proteoglycan production. Immunohistochemistry was also performed to assess types I and II collagen, decorin, keratan sulfate, and chondroitin sulfate content of ECM. Human anulus cells form multilayered colonies when cultured with minimal media and 20% fetal bovine serum in the micromass methodology. Stimulation of ECM production occurs when 5 ng/mL TGF-beta was added to the micromass media. TGF-beta also significantly increased the production of sulfated proteoglycans (P = 0.026). Under both control and TGF-beta-supplementation, the resulting micromass formed by anulus cells is not as compact as the micromass which results when stem cells cultured in chondrogenic media. Ultrastructural studies showed the presence of apoptotic cells and the presence of peroxisomes within cells. Immunohistochemical studies on production of type I collagen, decorin and keratan sulfate showed that there was localized production of these ECM components in focal regions; chondroitin sulfate and type II collagen, however, showed a more uniform overall production by cells within the micromass. Human anulus cells were successfully cultured under micromass conditions in nonchondrogenic media and with TGF-beta supplementation which increased ECM production. The resulting anulus cell micromass, however, was not as rounded or compact as that which occurs with routine chondrocyte micromass or stem cells induced into chondrocyte differentiation. The presence of peroxisomes noted on ultrastructural studies may reflect cell stress or uneven distribution of nutrition within the micromass during the 7-day micromass culture period. Immunohistochemical studies showed nonuniform ECM gene expression and production within the micromass, suggesting variable gene expression patterns with this culture method.